Transplantation of Cryopreserved Human Umbilical Cord Blood Mononuclear Cells Does Not Induce Sustained Recovery after Experimental Stroke in Spontaneously Hypertensive Rats. Issue 1 (January 2014) - Weise, Gesa; Lorenz, Marlene; Pösel, Claudia; Maria Riegelsberger, Ute; Störbeck, Veronika; Kamprad, Manja; Kranz, Alexander; Wagner, Daniel-Christoph; Boltze, Johannes
Previous studies have highlighted the enormous potential of cell-based therapies for stroke not only to prevent ischemic brain damage, but also to amplify endogenous repair processes. Considering its widespread availability and low immunogenicity human umbilical cord blood (HUCB) is a particularly attractive stem cell source. Our goal was to investigate the neurorestorative potential of cryopreserved HUCB mononuclear cells (MNC) after permanent middle cerebral artery occlusion (MCAO) in spontaneously hypertensive rats (SHR). Human umbilical cord blood MNC or vehicle solution was administered intravenously 24 hours after MCAO. Experimental groups were as follows: (1) quantitative polymerase chain reaction (PCR) of host-derived growth factors up to 48 hours after stroke; (2) immunohistochemical analysis of astroglial scarring; (3) magnetic resonance imaging (MRI) and weekly behavioral tests for 2 months after stroke. Long-term functional outcome and lesion development on MRI were not beneficially influenced by HUCB MNC therapy. Furthermore, HUCB MNC treatment did not change local growth factor levels and glial scarring extent. In summary, we could not demonstrate neurorestorative properties of HUCB MNC after stroke in SHR. Our results advise caution regarding a prompt translation of cord blood therapy into clinical stroke trials as long as deepened knowledge about its precise modes of action is missing.